Remote laser welding simulation for aluminium alloy manufacturing using computational fluid dynamics model - Raghad Ahmed Al-Aloosi; Zainab Abdul-Kareem Farhan; Ahmad H. Sabry (Institute of Advanced Engineering and Science, 2022)
The process of remote laser welding is simulated in this study to identify the keyhole-induced porosity generation mechanisms and keyhole. Three processes are simulated and discussed: laser power levels, laser-beam shaping configurations, and laser keyhole process. The simulation finding reveals that pore development is caused by strong melt flow behind the keyhole. As verification, the equivalent experimental test is also carried out. According to the findings, a welding speed with a high level helps to keep the keyholes released and prevents the flow of strong melt; a big advanced leaning-angle also provides inactive molten pool flow, making it difficult for bubbles to float to the backside of the molten pool. The conclusions of this study offer crucial insight into the method of porosity of aluminum (Al) alloys laser welding, as well as advice on how to avoid keyhole-induced porosity. It is also obtained that a smaller laser beam with constant power raises the velocity, welding pool depth, and liquid metal temperature.